Sistema domótico para el control de la temperatura ambiental y corporal dentro de los galpones del hato porcino de la ESPAM MFL - García Vera, Manuel Jacinto (2024)
The objective of this curricular integration work was to develop a home automation system to control environmental and body temperature in the pig herd sheds of the Veterinary Medicine program of the Manuel Félix López Higher Polytechnic Agricultural School of Manabí. For this, the EDER methodology was used, which consists of four phases: study, design, execution and review, which are aligned with each specific objective of the project. In the study phase, the interview technique was used to collect the necessary requirements for the system. In the next phase, a bibliographic review was carried out for the selection of hardware and software tools, and also for the communication architecture between the two. In the execution phase, prototyping and configurations of the system for its operation were carried out, and a web interface was developed using the XP methodology for data coding and storage. Finally, in the review stage, tests were carried out to validate the correct functioning of the system. As a result, it was shown that when the ambient temperature in the thermo cradle drops to 29 degrees, the heating mechanism turns on, and when it exceeds 32 degrees, it turns off, controlled by an actuator. In addition, an alert was implemented through the Telegram instant messaging platform to report abnormal body temperatures in piglets, all of which contributes to both energy and economic savings, as well as the well-being of the pigs. The web interface also allows you to view the environmental temperature data of the thermo cradles and the body temperature of the piglets in real time, and it also allows you to generate reports for more efficient data management.